Does Similar Whole Body Cooling Induce Gender-Specific Attention Stability Deterioration? (Baltic Journal of Sport and Health Sciences, 2015)
Background. There is evidence of greater whole body cooling induced unpredictable task switching and memory deterioration in men than in women; however, it is not known how whole body cooling affects attention stability. This study aimed at identifying if there are any gender-specific differences in the effect of cold water immersion-induced stress on attention stability.Methods. Thirteen men and thirteen women were exposed to acute cold stress by immersion in 14°C water until rectal temperature reached 35.5°C or for a maximum of 170 min. Thermoregulatory response (i.e. changes of body temperature and metabolic heat production) and attention stability response (i.e. Schulte table (less cognitively demanding task) and Schulte-Gorbov table (more cognitively demanding task)) were monitored.Results. During cold stress, body temperature variables decreased (p < .05) and did not differ between genders. Metabolic  heat  production  was  greater  (p